The Effect of Pruning Water Shoots on Growth and Yield of 2 Varieties of Eggplant (Solanum melongena L.) in Polybags - Nursabrina, Nazwa Asrita; Aini, Nurul; Nugroho, Agung (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2026)
Eggplant is a horticultural plant that can be cultivated in the highlands and lowlands in Indonesia. One of the cultivation techniques carried out on eggplant plants is pruning water shoots. Pruning makes the photosynthate produced by plants not only translocated to vegetative organs that are not needed. This study aims to determine the effect of pruning different water shoots on the growth and yield of eggplant plants. The study was carried out in Bogor Regency, West Java from April to August 2021. This study used a Randomized Block Design (RBD) consisting of 10 treatments and repeated 3 times. The observed parameters included growth observations and yield observations. The data obtained were analyzed using the ANOVA test and further tests were carried out using the Honest Significant Difference (HSD) test with a level of 5%. Based on the research, pruning treatment of several water shoots affects the growth and yield of eggplant plants. This was indicated by the increase in fruit weight, number of fruit, fruit diameter and length of eggplant. In the Yumi F1 variety pruning 3 shoots of water increased eggplant fruit weight by 52.7% and fruit number by 55.88% compared to the treatment without pruning. In the Pertiwi variety, pruning 3 shoots of water increased eggplant fruit weight by 33.81% and fruit number by 23.94% compared to the treatment without pruning.